Health-related quality of life findings from the Faroe Islands FIT FIRST FOR ALL school-based physical activity study - Olsen, Helgi Winther; Danielsen, Bára Berghamar; Sjúrðarson, Tórur; Antoft, Søren; Krustrup, Peter; Larsen, Malte Nejst; Mohr, Magni; Davidsen, Annika Helgadóttir; Skoradal, May-Britt (Frontiers in Sports and Active Living, 2025)
IntroductionThis study evaluated the FIT FIRST FOR ALL program's effects on health-related quality of life (HRQOL) among Faroese schoolchildren aged 7–16 years during a 10-week school-wide intervention.MethodsA non-randomized controlled design included 360 pupils from an intervention (INT, n = 179) and a control school (CON, n = 181). The INT group participated in 3 weekly 40-minute physical activity sessions over 10 weeks. HRQOL was assessed using KIDSCREEN-52, and changes were analyzed using linear mixed-effects models.ResultsA significant Time × Group interaction (P = 0.002) showed a 7% improvement in INT pupils' physical well-being, particularly among boys (8% increase, P < 0.001) and the youngest age group (7% increase, P = 0.006). No significant changes were observed in other HRQOL dimensions.DiscussionThe FIT FIRST FOR ALL program improved physical well-being, particularly among boys and younger age groups, showcasing its potential to influence selected dimensions of HRQOL through structured school-based physical activity. These findings suggest that tailoring the program to specific age and gender groups could further strengthen its scalability and effectiveness across diverse school settings.